2017
DOI: 10.1111/jace.14882
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth sodium titanate lead‐free piezoelectric coatings by thermal spray process

Abstract: Bismuth sodium titanate (BNT) piezoelectric ceramic coatings with dense morphology and single perovskite phase were fabricated by thermal spray process. The melting and crystallization behaviors of BNT near congruent composition and the effect of excess Bi composition were investigated by analyzing the heating-melting-cooling cycle for the application in thermal spray process. Crystal structure and morphology of the thermal sprayed BNT coatings were examined, and their electrical and electromechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The ceramic powder feedstocks and substrates preparation were reported in our previous publication . An Atmospheric Plasma Spraying system (9MC, Sulzer Metco Inc., Westbury, NY) was conducted at ambient pressure using Ar plasma with plasma power of 23 kW.…”
Section: Methodsmentioning
confidence: 70%
See 2 more Smart Citations
“…The ceramic powder feedstocks and substrates preparation were reported in our previous publication . An Atmospheric Plasma Spraying system (9MC, Sulzer Metco Inc., Westbury, NY) was conducted at ambient pressure using Ar plasma with plasma power of 23 kW.…”
Section: Methodsmentioning
confidence: 70%
“…As important smart materials, piezoelectric ceramic coatings have shown great application potentials in structure health monitoring, energy harvesting, etc. Research efforts have been reported on fabricating piezoelectric ceramic coatings by thermal spray process . By far, most of the thermal sprayed piezoelectric ceramic coatings had Pb‐based compositions, due to the outstanding electromechanical coupling properties of lead zirconate titanate (PZT) bulk ceramic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the extensive efforts and significant progress on developing lead‐free piezoelectric ceramics with competitive performance properties, they are regarded as the promising candidates to replace the market‐dominant PZT‐based materials for various applications . Recently, our group first reported thermal‐sprayed KNN‐based and bismuth sodium titanate (BNT)‐based lead‐free piezoelectric ceramic coating . The thermal‐sprayed coatings exhibited single phase of perovskite structure and strong piezoelectric response, with effective piezoelectric coefficient (d 33 ) up to 112 pm/V .…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Recently, our group first reported thermal-sprayed KNN-based and bismuth sodium titanate (BNT)-based lead-free piezoelectric ceramic coating. [29][30][31] The thermal-sprayed coatings exhibited single phase of perovskite structure and strong piezoelectric response, with effective piezoelectric coefficient (d 33 ) up to 112 pm/V. 29,31 The lead-free KNN-based or BNT-based ceramic compositions are environmentally friendly and thus suitable for wide implementation in largearea coating applications.…”
Section: Introductionmentioning
confidence: 99%